Security at the data link level in the Open Systems Interconnection Model (OSI) - Obando I, Christian; Obando I, Christian; Obando I, Christian (Corporación universitaria Americana, 2022)
Communications networks can provide an innumerableamount of services in an organization that will allow it to satisfy its most important needs, helping it to fulfill its organizational objectives more efficiently.in their computing devices can cause a great disadvantagefor these objectives. Layer two of the OSI model is considered one of the most important in the flow of information, since it is practically the starting point for communication with the rest of the layers of this model, so there is a need to study computer attacks on this layer and implement techniques to improve security in this layer.